A review of separation processes proposed for advanced fuel cycles based on technology readiness level assessments. (November 2019) - Baron, P.; Cornet, S.M.; Collins, E.D.; DeAngelis, G.; Del Cul, G.; Fedorov, Yu.; Glatz, J.P.; Ignatiev, V.; Inoue, T.; Khaperskaya, A.; Kim, I.T.; Kormilitsyn, M.; et al.
Abstract: The results of an international review of separation processes for spent nuclear fuel (SNF) recycling in future closed fuel cycles are reported. This study was made by the Expert Group on Fuel Recycling Chemistry (EGFRC) organised by the Nuclear Energy Agency (NEA) of the Organisation for Economic Co-operation and Development (OECD). A unique feature of this study was that processes were classified according to a hierarchy of separations aimed at different elements within spent fuel (uranium; uranium-plutonium co-recovery; minor actinides; high heat generating radionuclides) and also the Head-end processes, used to prepare the SNF for chemical separation, were included. Separation processes covered both wet (hydrometallurgical) and dry (pyro-chemical) processes. A bespoke methodology suitable for assessing the technological maturities of separation processes for SNF recycling was then designed based on the well-established Technology Readiness Level (TRL) scale but adapted for spent nuclear fuel separations. The innovative feature of this was the use of a matrix approach that enabled information on both the scale of testing and materials used in testing to be combined in the evaluation of the TRL. TRLs for the Head-end, hydrometallurgical and pyrochemical processes that had been reviewed by the study have been evaluated. It is clear that, whilst more R&D is needed in most cases to raise TRLs, suitable options exist to enable the recovery of all actinide elements plus the HHRs by wet or dry processes, even up to the extraordinarily difficult isolation of americium alone. The technology readiness levels (TRL) for most processes fall in the 'proof of principle' range with TRLs between 4 and 6, although this is an evaluation at the system level and some gaps in the individual process steps may still exist that strictly would reduce the overall TRL. That is, flowsheets have been proposed for processes and tested with active materials under increasingly relevant conditions, through to initial hot tests with small quantities of SNF. The results of this work were shown to be comparable to a parallel European study that evaluated TRLs for minor actinide partitioning processes. Graphical abstract: Image 1 Highlights: Results of an international study. Advanced reprocessing and minor actinide partitioning technologies. Review of progress in R&D on separation processes for advanced nuclear fuel cycles. Technology Readiness Level assessment of separation processes. Status of head-end, aqueous and pyro-chemical processes reviewed.